(9×9-6×6-a)+(13+28÷4)=5×10+3
Răspunsuri la întrebare
Răspuns de
0
(9×9-6×6-a)+(13+28:4)=5×10+3
(81-36-a)+(13+7)=50+3
(45-a)+20=53
45-a=53-20
45-a=33
a=45-33
a=12
(81-36-a)+(13+7)=50+3
(45-a)+20=53
45-a=53-20
45-a=33
a=45-33
a=12
Răspuns de
0
(9×9-6×6-a)+(13+28÷4)=5×10+3
(81-36-a)+(13+7)=50+3
45-a+20=53
45-a=53-20
45-a=33
a=45-33
a=12
(81-36-a)+(13+7)=50+3
45-a+20=53
45-a=53-20
45-a=33
a=45-33
a=12
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă
Engleza,
9 ani în urmă